Development of waqf forest in Indonesia: Brand equity analysis of Bogor waqf forest purchase intention - Firmannudin, Yusup; Lubis, Deni; Ali, Khalifah Muhamad (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aims to analyze the characteristics of respondents who donate, visit, or endow Bogor Waqf Forest and the influence of brand awareness, brand association, brand loyalty, and perceived quality on the purchase intention of Bogor Waqf Forest.Methodology – The data obtained in this study were primary data from questionnaires with 136 respondents and secondary data from literature studies such as foundations, journals, books, and related articles. The methods used in this research are descriptive analysis and structural equation modeling–partial least squares (SEM-PLS).Findings – The results of this study show that brand loyalty and perceived quality have a positive and significant influence.Implications – Maintaining and increasing perceived quality and brand loyalty so that consumer loyalty and perceptions remain high and well maintained.Originality – This research is original in measuring brand equity analysis of intention to purchase a Bogor Waqf Forest.